Character Education Based on Local Wisdom at SMA Negeri 1 Teladan Yogyakarta: A Model for Addressing Contemporary Challenges in the Digital Era - Zahro Ulfaturrohmatiririn; Khoirun Nisa; Riziq Syehab; Fiki Khoirotussiha (Journal of Islamic Education Management Research, 2023)
Purpose – This study aims to investigate the implementation of character education based on local wisdom at SMA Negeri 1 Teladan Yogyakarta and assess its impact on students' character development and academic performance in the context of contemporary challenges in the digital era. Design/methods– Utilizing a qualitative research methodology, the study focuses on an in-depth exploration of character education at SMA Negeri 1 Teladan Yogyakarta. Data collection methods include interviews, observation, and documentation, with a particular emphasis on how local wisdom is integrated into character education. Comparative analysis of the findings with existing literature on character education was conducted to assess the program's effectiveness. Findings – The study reveals a robust character education program at SMA Negeri 1 Teladan Yogyakarta, which includes character habituation during class, outside class, and in collaboration with parents and the community. The program positively influences students' enthusiasm for learning, collaboration, responsibility, and discipline, subsequently improving their academic performance. However, challenges such as student diversity and varying levels of character internalization were identified. Research implications/limitations – The research provides insights into the integration of local wisdom in character education, contributing to the discourse on character education in the digital era. Limitations include the focus on a single institution, which may affect the generalizability of the findings. Practical implications – The study offers a model for integrating character education based on local wisdom in educational institutions, highlighting the importance of a comprehensive approach that includes academic, extracurricular, and community aspects. Originality/value – This study contributes original insights into the field of character education by highlighting the integration of local wisdom at SMA Negeri 1 Teladan Yogyakarta. It presents a unique perspective on addressing contemporary challenges in education, particularly in the digital era, through a well-rounded character education program.